Determinants of Menstrual Hygiene Management Practices among Schoolgirls: A Cross-Sectional Study in the Savannah Region of Ghana - Mubarick Nungbaso Asumah; Abdulai Abubakari; Gifty Apiung Aninanya (Hindawi Limited, 2022)
Introduction. Menstruation is crucial in the reproductive lives of all women. The advent of menses in most settings is accompanied by physical and psychological health, religious, social, and cultural implications. The research intends to identify determinants of menstrual hygiene management (MHM) practices among adolescent girls in Junior High Schools in the West Gonja Municipality of the Savannah Region of Ghana. Methods. The study employed an analytical cross-sectional design with 430 adolescent schoolgirls selected through multistage sampling techniques. A structured questionnaire was used to collect data and analyzed using STATA version 14. A logistic regression model was run to determine the predictors of MHM practices. Results. The study discovered that 63.7% of the girls had sufficient knowledge of menstruation and menstrual hygiene. Almost all girls (97%) used some form of absorbent materials during menses, with over half of these girls (58.6%) using commercial sanitary pads, 30.5% using cloth, 3.7% using cotton, and 4.2% using tissue papers with 3.0% reported not using any absorbent material. Only 44.4% reported reusing their absorbent materials. Out of which, the majority (88.5%) of the schoolgirls cleaned their reusable absorbent material using soap and water with 77.5% drying absorbent materials in the sun. Overall, 84.9% practiced good MHM. Type of school [Adjusted Odds Ratio (AOR) =6.0; 95% Confidence Interval (CI) (2.64-13.59)], pocket money [AOR =2.5; 95% CI (1.27-4.86)], and residence [AOR =2.8 95% CI (1.55-5.18)] were the most significant determinants of menstrual hygiene management practice. Conclusion. About two-thirds of the schoolgirls are knowledgeable in menstrual hygiene but access to management materials is problematic whereas approximately half of the girls have access to sanitary pads and the rest resort to the use of cloth and cotton. Pocket money and residential status were the most important predictors of the menstrual hygiene management. The government initiative to provide schoolgirls with sanitary pads could go a long way to improve menstrual hygiene management if implemented across all schools in Ghana, particularly in rural areas.